Dampak Perkawinan Usia Dini terhadap Kesejahteraan Keluarga (Studi Kasus di Kecamatan Wonoasih Kota Probolinggo) - Zahroil Warda; Ahmad Syaifuddin Romli (Posita: Jurnal Hukum Keluarga Islam, 2025)
The phenomenon of early marriage remains prevalent in various regions of Indonesia, including Wonoasih District, Probolinggo City, despite the government’s regulation of the minimum marriage age through Law Number 16 of 2019. This study aims to analyze the impact of early marriage on family welfare, focusing on economic aspects, psychological harmony, as well as children’s education and future. The research employed a qualitative method with a case study approach through interviews, observation, and documentation involving 6 female informants who were married at the age of 16–19, with educational backgrounds ranging from elementary to senior high school, and occupations as housewives, factory workers, and domestic helpers. The results indicate that early-married couples experience economic vulnerability due to low educational attainment and unstable income, which affects their ability to meet basic family needs. Psychologically, emotional immaturity leads to frequent household conflicts, stress, and even divorce. Furthermore, the interruption of education, particularly among women, reduces the family’s human capital accumulation, while children born from early marriages are at risk of developmental delays due to suboptimal parenting. These conditions affirm that early marriage has multidimensional consequences that weaken family welfare. Therefore, integrated interventions through education, economic empowerment, and cultural value strengthening are necessary to prevent and mitigate its negative impacts.